P788 Comparison of vaginal speculum and non-speculum specimens in the diagnosis of trichomonas vaginalis. (14th July 2019) - Obunge, Orikomaba; Oboro, Ibinabo; Onyejepu, Nneka; Alex-Wele, Mary
Abstract : Background: Trichomoniasis is the most prevalent non-viral sexually transmitted infection worldwide. In Nigeria, prevalence ranges from 5% to 15%. Apart from being a key biologic indicator of sexual activity, it's been associated with the transmission of Human Immunodeficiency virus. The use of vaginal speculum is traditionally required for specimen collection. The limited application of this step in various primary health care facilities in resource-poor settings due to difficulties with sterilization of speculae among others, has grossly reduced the offer of testing for Trichomoniasis. Self-collected vaginal swab could be an acceptable alternative specimen for diagnosis of trichomoniasis in low income settings. We compared the yield of Trichomonas vaginalis from speculum and non-speculum based specimens. Methods: 500 women between 18–45 years presenting with abnormal vaginal discharge in two health care facilities in Rivers State, Nigeria, were enrolled. Three specimens were collected from each woman; two non-speculum based/non-invasive and the third, speculum based. Microscopists were trained and the procedure standardized. Wet mount microscopy was performed on all specimens within thirty minutes of collection. Three Microscopists examined each specimen independently. All infected patients were managed according to existing guidelines. Ethical approval was obtained and data analyzed using SPSS version 20. Results: Median age of participants was 31 years. Of the 500 women, 53 were infected giving an overall prevalence of 10.6%. Using the speculum-based specimens, 90.5% (48) of infected women were detected while 83.0% (44) and 30.1% (16) were detected using the self-collected swab and first void urine respectively. Interestingly, first void urine was able to detect five (5) more cases that were not detected by the speculum-based method. Conclusion: In low income settings, use of self-collected swabs in combination with first void urine is likely to increase detection rate of Trichomonas vaginalis when compared with the use of vaginal speculum only. Disclosure: No significant relationships.